Causal physics photons by non-interactions of waves - Roychoudhuri, Chandrasekhar (CRC Press, Taylor & Francis Group, 2014)
A Causal Photon Model for Optical Scientists & EngineersCausal Physics: Photons by Non Interactions of Waves redefines the mathematical Superposition Principle as an operational Superposition Effect; which is the measurable physical transformation experienced by a detector due to stimulations induced by multiple waves simultaneously acting on the detecting dipoles. This light-matter interaction process driven model emerges naturally by incorporating the observed properties, Non-Interaction of Waves (NIW) and quantized